PROPULSION SYSTEM DESIGN FOR THE INDONESIAN SEMI HIGH SPEED TRAIN - Shalahuddin, Lukman; Putranto, Kartiko E.; Eskayudha, Dimas B. (Majalah Ilmiah Pengkajian Industri, 2019)
This paper describes a study on the development of methodology to select the most appropriate technology, and the most optimum design and configuration for the propulsion system of the semi-high speed intercity train that will be operated on the Jakarta-Surabaya corridor. It also describes the method to calculate resistance loads  and tractive forces and hence the power required to propel the train along the specified route within targeted time. Among the output of this study is a recommendation for the most optimum propulsion system with basic/ main parameters for main components such as diesel engine, traction motor and the possibility of Diesel Electric Multiple Unit (DEMU) Hybrid battery system.